The European Union’s Initiative towards Implementing European Public Sector Accounting Standards - Estimated Advantages and Benefits versus Disadvantages and Costs - Michałowska-Mazur, Antonina (Studia Oeconomica Posnaniensia, 2017)
Standardisation and the harmonisation of accounting rules are common processes in a globalizing world, present in both private and public sectors. Global companies rely on International Financial Reporting Standards and public entities follow International Public Sector Accounting Standards. The European Union also formulated a basis for the national accounting regulation of its member states: directives on the annual accounts of certain types of companies and on consolidated accounts. Economic breakdown in 2010-2011 revealed a lack of mechanisms to monitor public deficit and debt statistics, which is essential for the functioning of an economic and monetary union. As a result of the fiscal crisis in Europe, an idea has been developed of implementing common accounting standards for the European public sector. The initiative to develop and implement EPSAS (European Public Sector Ac-counting Standards) as a tool enabling sound and sustainable public finance management brings both benefits and costs. The main advantages refer to high-quality financial information: improved comparability and the transparency of data. On the other side, EPSAS would implicate substantial costs of public accounting reorganisation (a.o. IT modernisation, human resources training). Since the EPSAS project is still in an initial phase, many detailed questions on the possible implementation of the formula remain under consideration.